Adaptation and divergence in edaphic specialists and generalists: serpentine soil endemics in the California flora occur in barer serpentine habitats with lower soil calcium levels than serpentine tolerators. Issue 5 (9th May 2019) - Sianta, Shelley A.; Kay, Kathleen M.
Abstract : Premise: Adaptation to harsh edaphic substrates has repeatedly led to the evolution of edaphic specialists and generalists. Yet, it is unclear what factors promote specialization versus generalization. Here, we search for habitat use patterns associated with serpentine endemics (specialists) and serpentine tolerators (generalists) to indirectly test the hypothesis that trade‐offs associated with serpentine adaptation promote specialization. We predict that (1) endemics have adapted to chemically harsher and more bare serpentine habitats than tolerators, and (2) edaphic endemics show more habitat divergence from their sister species than tolerators do among on‐ and off‐serpentine populations. Methods: We selected 8 serpentine endemic and 9 serpentine tolerator species representing independent adaptation to serpentine. We characterized soil chemistry and microhabitat bareness from one serpentine taxon of each species and from a paired nonserpentine sister taxon, resulting in 8 endemic and 9 tolerator sister‐taxa pairs. Results: We find endemic serpentine taxa occur in serpentine habitats averaging twice as much bare ground as tolerator serpentine taxa and 25% less soil calcium, a limiting macronutrient in serpentine soils. We do not find strong evidence that habitat divergence between sister taxa of endemic pairs is greater than between sister taxa of tolerator pairs. Conclusions: These results suggest serpentine endemism is associated with adaptation to chemically harsher and more bare serpentine habitats. It may be that this adaptation trades off with competitive ability, which would support the longstanding, but rarely tested, competitive trade‐off hypothesis.